Registration of range images using a histogram based metric (2012)
In this paper, a new approach for coarse registration of triangular meshes for three-dimensional object reconstruction is proposed by using the shape-index measure for topological description and the Earth Mover's Distance (EMD) metric for region similarity estimation. Two of its main advantages are independence from initial pre-alignment and spatial transformation, obtaining a more accurate registration regardless of the initial viewing position.